2019
DOI: 10.24843/eja.2019.v26.i03.p08
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Tarif Pajak, Pemahaman Perpajakan, dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak UMKM

Abstract: Usaha Mikro, Kecil dan Menengah (UMKM) merupakan salah satu sektor yang berpotensimemberikan sumbangsih terhadap penerimaan pajak Negara. Kepatuhan wajib pajakUMKM masih sangat rendah, khususnya kepatuhan wajib pajak UMKM yang terdaftar diKPP Pratama Singaraja pada tahun 2015-2017 belum mencapai 50%. Tujuan penelitian iniadalah untuk menguji pengaruh tarif pajak, pemahaman perpajakan dan sanksi perpajakanterhadap kepatuhan wajib pajak UMKM. Teori yang digunakan dalam penelitian ini adalahtheory of planned beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
26

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(82 citation statements)
references
References 0 publications
4
18
0
26
Order By: Relevance
“…Thus it was concluded that there was a significant influence between the understanding of taxpayer compliance at a significance level of under 5%. The results of this study support research conducted by Luh Putu Gita Cahyani and Naniek Novianri [3] which states that understanding has a positive effect on UMKM taxpayer compliance. and also supports research conducted by Debby Cornelia and Icha Fajrian [11] which states that understanding has a positive effect on compliance after the adoption of Government Regulation No, 23 of 2018 on UMKM in Palembang.…”
Section: Influence Of Understanding On Taxpayer Compliancesupporting
confidence: 88%
See 2 more Smart Citations
“…Thus it was concluded that there was a significant influence between the understanding of taxpayer compliance at a significance level of under 5%. The results of this study support research conducted by Luh Putu Gita Cahyani and Naniek Novianri [3] which states that understanding has a positive effect on UMKM taxpayer compliance. and also supports research conducted by Debby Cornelia and Icha Fajrian [11] which states that understanding has a positive effect on compliance after the adoption of Government Regulation No, 23 of 2018 on UMKM in Palembang.…”
Section: Influence Of Understanding On Taxpayer Compliancesupporting
confidence: 88%
“…Thus it was concluded that there was a significant influence between tax rates on taxpayer compliance at a significance level of under 5%. The results of this study support research conducted by Luh Putu Gita Cahyani and Naniek Novianri [3] which states that tax rates have a positive effect on UMKM taxpayer compliance. This test also supports the decision making process, which is whether the taxpayer must comply or not is influenced by the intention of the taxpayer himself in taking action to comply with tax obligations.…”
Section: Influence Of Tax Rates On Taxpayer Compliancesupporting
confidence: 88%
See 1 more Smart Citation
“…Baik sanksi administrasi maupun sanksi pidana, keduanya justru dapat memberatkan usaha yang sedang dijalankan, sehingga harus dihindari. Menurut Cahyani & Noviari (2019) pemahaman pajak, tarif pajak, dan sanksi pajak berpengaruh terhadap kepatuhan pajak. Menurut Anwar & Syafi qurrahman (2016) sosialisasi pajak dan pengetahuan pajak berpengaruh terhadap kepatuhan wajib pajak.…”
Section: Pendahuluanunclassified
“…In the study of Atawodi and Ojeka (2012) stated that exorbitant tax rate cause taxpayer non-compliance. In the research of Cahyani andNaniek (2019), Tawas, et al (2016), Helhel and Ahmed (2014), and Atawodi and Ojeka (2012) examine the tax rate on taxpayer compliance. The results of previous studies stated that the tax rate has significant effect taxpayer compliance.…”
Section: Effect Of Tax Rates On Taxpayer Compliancementioning
confidence: 99%